Dual catalysis with an N‐heterocyclic carbene and a Lewis acid: Thermally latent precatalyst for the polymerization of ε‐caprolactam. Issue 22 (3rd October 2020) - Altmann, Hagen J.; Steinmann, Mark; Elser, Iris; Benedikter, Mathis J.; Naumann, Stefan; Buchmeiser, Michael R.
Abstract: So far, the earlier reported strong correlation between basicity of an N ‐heterocyclic carbene (NHC) and its reactivity in poly(ε‐caprolactam) (PA6) synthesis resulted in a substantial limitation of applicable carbenes. Here, to overcome this issue, 1, 3‐dimethylimidazolium‐2‐carboxylate, an easily accessible, air and moisture‐stable NHC, was applied as thermally latent initiator. In order to compensate for its low basicity, reactivity was enhanced by the addition of both a Lewis acid and an activator to ease the initial polymerization step. The resulting mixtures of ε‐caprolactam, the CO2 ‐protected NHC, a Lewis acid and N ‐acylazepan‐2‐one constitute homogeneous, thermally fully latent "single‐component" blends for the anionic polymerization‐based synthesis of PA6. They can be stored both in the liquid and solid state for days and months, respectively, without any loss in activity. The role of the Lewis acid as well as technical implications of the prolonged pot‐times are discussed. Abstract : The use of 1, 3‐dimethylimidazolium‐2‐carboxylate together with N ‐acetylazepan‐2‐one enables the synthesis of polyamide 6 from fully latent, fast solidifying, single‐component mixtures with ε‐caprolactam (CLA) with little effort in precatalyst synthesis. The one‐pot synthesized, CO2 protected N ‐heterocyclic carbene, despite its lower basicity compared to lactams, initiates the polymerization at elevated temperatures. Polymerization is further accelerated by the addition of Lewis acids or diisocyanate adducts of ε‐CLA.